2009
DOI: 10.1002/ldr.911
|View full text |Cite
|
Sign up to set email alerts
|

How can we control erosion of roadslopes in semiarid mediterranean areas? Soil improvement and native plant establishment

Abstract: Road building triggers vegetation and soil degradation which affects road safety. We present conclusive results in terms of roadslope protection against erosion from several studies performed on semiarid roadslopes since 2000 (in Eastern Spain). We aim to (1) improve our understanding about slope and vegetation factors which control soil erosion and plant colonisation on semiarid roadslopes; (2) assess the effectiveness of topsoiling, hydroseeding and species selection in the protection of soil against erosion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
1
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 29 publications
7
50
1
4
Order By: Relevance
“…Other studies investigated the influence of organic amendment on the moisture of eroded soil (in particular Ojeda et al, 2003;Hueso-González et al, 2015), but the context of soils, types of amendment and slope gradi- Table 1). ents were significantly different, and the comparison is not relevant. According to Bochet et al (2007), soil water availability after rainfalls occurring during the germination period played a major role in seed germination. These authors and Crosaz (1995) also suggested that the species' ability to germinate under drought conditions could indicate a species' potential for success under semiarid conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies investigated the influence of organic amendment on the moisture of eroded soil (in particular Ojeda et al, 2003;Hueso-González et al, 2015), but the context of soils, types of amendment and slope gradi- Table 1). ents were significantly different, and the comparison is not relevant. According to Bochet et al (2007), soil water availability after rainfalls occurring during the germination period played a major role in seed germination. These authors and Crosaz (1995) also suggested that the species' ability to germinate under drought conditions could indicate a species' potential for success under semiarid conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Planting and seedling methods for installing vegetation on slopes are therefore required. Such methods have already been tested on several other eroded lands (Reubens et al, 2009;Bochet et al, 2010;Fernández et al, 2012;Commander et al, 2013;Lee et al, 2013), but these studies did not apply to our climatic, topographic and pedological conditions, and the studied plant species are not appropriate or currently available. Therefore, the main issue for practitioners is to find the adequate solution to develop vegetation cover on gully slopes.…”
Section: Breton Et Al: Effects Of Wood Chip Amendments On the Revmentioning
confidence: 99%
“…Laynez-Garsaball et al (2007) determinaron que bajos potenciales agua del sustrato afectan el crecimiento de plántulas de Zea mays L., independiente del tamaño de la semilla. Por otro lado Bochet et al (2010) encontraron que las especies exitosas para colonizar taludes en ambiente semiárido mediterráneo presentan tasas y velocidades de germinación más altas que las especies no exitosas, en condiciones experimentales de baja disponibilidad hídrica. A su vez reportaron que la mayor parte del tiempo los estratos superiores de los taludes permanecen secos, además de secarse rápidamente después de eventos de precipitación.…”
Section: Resultados Y Discusiónunclassified
“…Tormo et al (2008) encontraron que el estrés hídrico es el factor más influyente en el éxito de establecimiento y permanencia de las especies en terraplenes de clima mediterráneo. Por otro lado, Bochet et al (2010) sostienen que la disponibilidad de micrositios es un factor limitante para la instalación de las especies, a su vez lograron los mejores resultados aumentando la rugosidad de la superficie del talud e hidrosembrando especies nativas seleccionadas.…”
Section: Introductionunclassified
“…The species composition of the commercial seed mixture used in the hydroseeding treatments is shown in table 2; the choice of a commercial mixture was recently supported by Oliveira et al (2011) who revealed some drawbacks in the use of native species as relatively slow germination, seasonality, and seed dormancy-breaking requirements. However, we note that many studies recommend the use of native species in performing hydroseeding (Paschke et al, 2000;Matesanz et al, 2006;Tinsley et al, 2006;Tormo et al, 2007;Bochet et al, 2010aBochet et al, , 2010bGarcia-Palacios et al, 2010;Madruga-Andreu et al, 2011) comparing them to commercial ones, and deriving from native species a better plant cover in exchange for a higher initial cost.…”
Section: Experimental Design and Hydroseeding Mixturesmentioning
confidence: 92%